Karateristik Kepemimpinan Dalam Pendidikan Islam Untuk Menjawab Tantangan Revolusi Industri 4.0 - Ari Susandi (Proceedings of Annual Conference on Islamic Educational Management, 2022)
Islamic education in Indonesia currently still needs to be added and improved in quality with good prospects in management in an institution as well as intellectual teaching resources as well as quality stakeholders as well as an attractive and comfortable learning environment to run well and optimally. The industrial revolution 4.0 is in a situation to create individual competitiveness both in the fields of science, technology and the ability to synergize in realizing a progressive Indonesia. Therefore, the characteristics of a good and ideal leader by applying four characters are open, loyal, integrity and professional, because this open character is how a leader must always be able to accept criticism and suggestions, loyal character is how the leader can always understand and understand colleagues in the project. In an institution, the character of integrity is a leader who always provides a good and interesting example with the spirit of completing tasks and this professional character is how the leader must be wise and sportsmanship in completing tasks and be able to embrace the stakeholders in the institution with four aspects of character, totality, imaginative and professional. By applying the four characteristics above, it will be able to give birth to a competent leadership figure who will give birth to highly competitive student stakeholders who can change from leadership characteristics in the past so that they can answer the VUCA (Volatile, Uncertain, Complex and Ambiguo) situation.